Community Compliance Intention to Pay Zakat at BAZNAS Serang Regency; Testing the Impact of Subjective Norms and Attitudes - Najmudin Najmudin; Moh Ainun Najib; Abdurohim Abdurohim (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine (1). The effect of subjective norms on people's compliance intentions to pay zakat at BAZNAS Serang Regency. (2). The effect of attitudes on compliance behavior in paying zakat at BAZNAS Serang Regency, and (3) The effect of subjective norms and attitudes on compliance intentions to pay zakat at BAZNAS Serang Regency. The object of this research is the people of Serang Regency who consistently and continuously pay zakat at BAZNAS Serang Regency. The research method used is quantitative. Data collection techniques using a questionnaire. The data were analyzed using the multiple linear regression method through the SPSS version 23 program. The results of this study indicate that (1). Subjective norms have a positive and significant effect on people's compliance intentions to pay zakat at BAZNAS Serang Regency. (2). Attitudes have a positive and significant effect on compliance intentions to pay zakat at BAZNAS Serang Regency, and (3) Subjective norms and attitudes have a positive and significant effect on compliance intentions to pay zakat at BAZNAS Serang Regency. The total contribution of the influence of subjective norms and attitudes towards compliance intentions to pay zakat at BAZNAS Serang Regency is 52 percent, while the rest is influenced by other variables not examined in this study.